Pseudoseizures with urinary incontinence in a child with Neuromyelitis optica: a rare association - A., Chamelee; K., Raman; Nambi, Shanthi; Chandraleka, G. S. (International Journal of Research in Medical Sciences, 2019)
Background: Paroxysmal non epileptic events or pseudoseizures are common seizure mimics in children. But occasionally PNES events can present or coexist along with organic neurological disorders complicating the clinical scenario posing great challenges for diagnostic and therapeutic implications. Unusual symptomatology in PNES like frothing, tongue bite or urinary incontinence can be seen in PNES. Here, we present a rare case of pseudoseizures with urinary incontinence in a child with Neuromyelitis optica which posed a challenge for diagnosis and proper management with a favourable clinical outcome. A 14 years old girl who was known diagnosed case of Neuromyelitis optica on treatment with oral steroids presented with a history of repeated attacks of involuntary movements affecting all four limbs preceded by a feeling of fear and pain and these events were associated with urinary incontinence. Electroencephalogram and magnetic resonance imaging were performed on the patient. Ictal video EEG confirmed the diagnosis of pseudoseizures. Neuropsychological evaluation was performed which revealed multiple psychological stressors. Repeated counseling sessions and psychotherapy provided significant improvement in the form of remission of pseudoseizures.